Integrability of the Fourier Transforms of \( α \)-Monotone Functions - Mukanov, Askhat (Eurasian Mathematical Journal, 2015)
We define a class of \( α \)-monotone functions. We study of integrability conditions of the Fourier transforms of functions from this class.